Validação das emoções na infância: vergonha, ansiedade e sintomatologia depressiva - Lourenço, Sara (2010)
The study of emotions has been considered crucial to understand the psychological functioning. Available studies on how emotions reach a paramount role in the individuals’ life, based on the relational experience with parents in childhood, base themselves on memories of that period recorded and evoked by individuals in adulthood. With the objective of studying in loco how emotions influence individuals’ life since early on (even during childhood), a set of studies was performed in a sample of 188 children from 8 to 12 years old. The results showed that mothers perceived as punitive of their children’s emotions, activate in children feelings of shame. The development of this emotion significantly contributes to the presence of psychopathology, specifically the presence of depressive and anxiety symptoms.